Ingestible Osmotic Pill for In Vivo Sampling of Gut Microbiomes - Nejad, Hojatollah Rezaei; Oliveira, Bruno C. M. [UNESP]; Sadeqi, Aydin; Dehkharghani, Amin; Kondova, Ivanela; Langermans, Jan A. M.; Guasto, Jeffrey S.; Tzipori, Saul; Widmer, Giovanni; Sonkusale, Sameer R. (Wiley-Blackwell, 2019)
Technologies capable of noninvasively sampling different locations in the gut upstream of the colon enable new insights into the role of organ-specific microbiota in human health. Herein, an ingestible, biocompatible, battery-less, 3D-printed microengineered pill with an integrated osmotic sampler and microfluidic channels for in vivo sampling of the gut lumen and its microbiome upstream of the colon is discussed. The pill's sampling performance is characterized using realistic in vitro models and validated in vivo in pigs and primates. Herein, the results show that the bacterial populations recovered from the pill's microfluidic channels closely resemble the bacterial population demographics of the microenvironment to which the pill is exposed. Herein, it is believed that such lab-on-a-pill devices revolutionize the understanding of the spatial diversity of the gut microbiome and its response to medical conditions and treatments.
Keywords: biomedical devices; lab-on-a-chip; microbiomes; microfluidics; smart pills